The heterogeneous effect of marijuana decriminalization policy on arrest rates in Philadelphia, Pennsylvania, 2009–2018. (1st July 2020) - Tran, Nguyen K.; Goldstein, Neal D.; Purtle, Jonathan; Massey, Philip M.; Lankenau, Stephen E.; Suder, Joanna S.; Tabb, Loni P.
Highlights: Marijuana decriminalization has the potential to reduce health inequities. The heterogeneous effect of marijuana decriminalization has received limited attention. Decriminalization significantly reduced the risk of marijuana arrests overall. Absolute/relative racial disparities decreased for possession-based arrests. Relative racial disparities increased for sales/manufacturing-based arrests. Abstract: Background: Marijuana decriminalization holds potential to reduce health inequities. However, limited attention has focused on assessing the impact of decriminalization policies across different populations. This study aims to determine the differential effect of a marijuana decriminalization policy change in Philadelphia, PA on marijuana arrests by demographic characteristics. Methods: Using a comparative interrupted time series design, we assessed whether the onset of marijuana decriminalization in Philadelphia County was associated with reduction in arrests rates from 2009 to 2018 compared to Dauphin County. Stratified models were used to describe the differential impact of decriminalization across different demographic populations. Results: Compared to Dauphin, the mean arrest rate for all marijuana-related crimes in Philadelphia declined by 19.9 per 100, 000 residents (34.9% reduction), 17.1 per 100, 000 residents (43.1% reduction) for possession, and 2.8 per 100, 000 resident (15.9% reduction) for sales/manufacturing. Arrest rates also differed by demographic characteristics post-decriminalization. Notably, African Americans had a greater absolute/relative reduction in possession-based arrests than Whites. However, relative reductions for sales/manufacturing-based arrests was nearly 3 times lower for African Americans. Males had greater absolute/relative reduction for possession-based arrests, but lower relative reduction for sales/manufacturing-based arrests compared to females. There were no substantial absolute differences by age; however, youths (vs. adults) experienced higher relative reduction in arrest rates. Conclusions: Findings suggest an absolute/relative reduction for possession-based arrests post-decriminalization; however, relative disparities in sales/manufacturing-based arrests, specifically for African Americans, increased. More consideration towards the heterogeneous effect of marijuana decriminalization are needed given the unintended harmful effects of arrest on already vulnerable populations.